Genetic analysis of a successful repatriation programme: giant Galápagos tortoises - Milinkovitch, Michel C.; Monteyne, Daniel; Gibbs, James P.; Fritts, Thomas H.; Tapia, Washington; Snell, Howard L.; Tiedemann, Ralph; Caccone, Adalgisa; Powell, Jeffrey R. (Proceedings of the Royal Society. B, Biological sciences, 2004)
As natural populations of endangered species dwindle to precarious levels, remaining members are sometimes brought into captivity, allowed to breed and their offspring returned to the natural habitat. One goal of such repatriation programmes is to retain as much of the genetic variation of the species as possible. A taxon of giant Galápagos tortoises on the island of Española has been the subject of a captive breeding-repatriation programme for 33 years. Core breeders, consisting of 12 females and three males, have produced more than 1200 offspring that have been released on Española where in situ reproduction has recently been observed. Using microsatellite DNA markers, we have determined the maternity and paternity of 132 repatriated offspring. Contributions of the breeders are highly skewed. This has led to a further loss of genetic variation that is detrimental to the long-term survival of the population. Modifications to the breeding programme could alleviate this problem.